Relationship between Artificial Intelligence (AI) and Teachers’ Education Programmes for Sustainable National Development in Vocational and Technical Education in Public Schools of North Central Nigeria - Agwom, Saleh Dauda; Felix, Ogah Felix Mathew; Oluseye, Adepoju Adediran (Kashere Journal of Education, 2025)
This study examined the relationship between artificial intelligence (AI) and teachers' education programs for sustainable national development in vocational and technical education (VTE) in public schools across the Northern Central Zone of Nigeria. The focus was on how AI-driven pedagogical tools and digital innovations contribute to the training and retraining of teachers within the National Certificate in Education (NCE) and Professional Diploma in Education (PDE) frameworks. Using a descriptive survey design, data were collected from lecturers, pre-service, and in-service teachers across Colleges of Education and Faculties of Education that offer technical and vocational programmes. A sample of 385 respondents was selected from a population of 60,247 using Krejcie and Morgan’s formula. A structured questionnaire with a Content Validity Index (CVI) of 0.86 and a reliability coefficient of 0.82 (Cronbach Alpha) was employed. The data were analysed using descriptive and inferential statistics at a 0.05 level of significance. The study found a significant relationship between AI integration and the quality of teacher education programs that enhances skill acquisition, innovation, and employability among students of vocational and technical education. However, challenges such as poor digital infrastructure, insufficient AI literacy among teacher trainers, low funding, and resistance to innovation constrained full implementation. The study finds that adding AI to VTE teacher training can help Nigeria reach its long-term national development goals faster by making workers more ready, more tech-savvy, and more productive in the workplace. It recommends the inclusion of AI pedagogy in NCE and PDE curricula and the establishment of digital learning laboratories in teacher training institutions.